Biochemical markers of bone resorption are present in human milk: implications for maternal and neonatal bone metabolism. (28th September 2014) - Bouroutzoglou, Maria; Malamitsi‐Puchner, Ariadne; Boutsikou, Maria; Marmarinos, Antonios; Baka, Stavroula; Boutsikou, Theodora; Hassiakos, Dimitrios; Gourgiotis, Dimitrios; Briana, Despina D.
Abstract Aim This study investigated breast milk and maternal serum concentrations of biochemical markers of bone resorption, which may be implicated in both maternal and neonatal bone metabolism. Methods Tests were carried out on 85 parturients 3–4 days after they gave birth. We measured their breast milk and serum concentrations for soluble receptor activator of nuclear factor kappaB ligand (sRANKL) and cross‐linked N‐telopeptide of type I collagen (NTx). The sRANKL and NTx concentrations were associated with several perinatal parameters. Results Soluble receptor activator of nuclear factor kappaB ligand was detectable in breast milk at considerably lower concentrations than in maternal serum (p < 0.001), and these breast milk sRANKL concentrations were decreased in maternal diabetes (b = −0.366, 95% CI −0.622 to −0.110, p = 0.006). Breast milk NTx concentrations were higher in exclusive lactation (b = 0.269, 95% CI 0.014–0.524, p = 0.039), but lower in Caesarean sections (b = −0.224, 95% CI −0.428 to −0.019, p = 0.032). Conclusion Soluble receptor activator of nuclear factor kappaB ligand is downregulated in breast milk, particularly in the case of diabetes. Breast milk NTx upregulation characterises exclusive lactation, and its downregulation characterises Caesarean section deliveries. Nutritional interventions in foetal life and early infancy may programme adult bone health and ameliorate diseases with developmental origins, such as osteoporosis.